(untitled) - Barsoux, Jean-Louis (New York, N.Y., 2000)
In this time INSEAD has grown to be the leading business and management school in Europe, and one of the most successful and influential in the world. This book is a business study and history of INSEAD which details how this success was achieved, and goes on to relate the story of the school to the management themes of leadership, teamworking and innovation. Available in English and French editions.
Keywords: Trường kinh doanh,Business schools; Lịch sử,History; Nước Pháp,France